Experimentally Increasing Self-Continuity Improves Subjective Well-Being and Protects against Self-Esteem Deterioration from an Ego-Deflating Task. Issue 2 (3rd April 2019) - Sokol, Yosef; Serper, Mark
ABSTRACT: 'Self-continuity, ' or 'continuous identity' is the sense of cross-temporal persistence of identity and is associated with positive mood and decreased suicidality. Few studies have examined whether self-continuity is affected by reviewing cross-temporal patterns of personality traits and if increasing self-continuity improves subjective well-being. Study 1 examined the effects of writing about patterns of cross-temporal personality traits and found that this led to increased future self-continuity and reported life satisfaction. Study 2 examined the effects of a structured interview about cross-temporal personality traits and visualizing past/future selves and found that this led to increased future self-continuity, satisfaction with life, positive mood, and less deterioration in self-esteem after an impossible anagram task. These results suggest that increasing self-continuity may improve psychological health and well-being by increasing identity stability.